Vertical housing and sense of community: Almendares in Sagrada Familia - Cubillo Monge, Valeria Jesús (2025)
Introduction: This research was carried out between March and November of the year 2023 in the Almendares I condominium and the Sagrada Familia neighborhood, San José, Costa Rica. The argument of the research is that the institutional planification that Almendares I had negatively affects the sense of community between the Almendares I and Sagrada Familia’s inhabitants. Objective: Establish the planification of the condominium’s incidence exercised by the institutions on the sense of community of the Almendares I´s inhabitants towards the Sagrada Familia neighborhood. Method and technique: A qualitative methodology was used, with which semi-structured interviews and focus groups were carried out. Eight interviews were done with Almendares I’s population, eight with the Sagrada Familia neighborhood population, one focus group, and, additionally, a MIVAH civil servant was interviewed. Result: The perceptions that the neighborhood’s inhabitants have towards the condominium and the prejudices that the Almendares I’s inhabitants had towards the neighborhood affects the integration between both populations, which has avoided the generation of attachment towards the neighborhood. Conclusions: It was determined that the way in which the MIVAH planned the Almendares I condominium has had a negative impact on its inhabitants’ sense of community towards the Sagrada Familia neighborhood.